Leader openness, nationality dissimilarity, and voice in multinational management teams - Tröster, Christian; van Knippenberg, Daan (Journal of International Business Studies, 2012)
We argue that leader-directed voice (i.e., communicating critical suggestions for change to the leader) is a relational phenomenon, and that it is affected by an inherent feature of multinational teams: members’ (dis)similarities in nationality. We tested our hypotheses in a sample of middle managers who were working in multinational teams. The results of this study show that leaders of multinational teams are more likely to profit from the local know-how of employees from underrepresented nationalities when they are open to their ideas, and when they have the same nationality. The study also shows that the effects of being open to employees’ ideas and sharing the same nationality are mediated by affective commitment and psychological safety, respectively. We discuss how, even though the current relational demography perspective with its dichotomous understanding of (dis)similarity is not suited to capture the dynamics of cultural differences, it does set the stage for future studies to examine the cultural dynamics behind an individual's experience of being different from other team members in multinational teams. We also discuss the practical implications of these findings for multinational companies.